Exploring the nexus between entrepreneurship and international business: A case study of Bhutan - Bhuwan Shrivastava; Pem Dechen Topgay; Pema Lhaden Topgay; Lhaki Dema; Sumita Dave (Agora International Journal of Economical Sciences (AIJES), 2024)
This study delves into the relationship between entrepreneurship and international business in Bhutan, a small, landlocked kingdom that primarily depends on agriculture and hydropower. It aims to assess the current state of entrepreneurship in Bhutan, explore the trends in international trade involving Bhutanese businesses, and pinpoint the challenges and opportunities that Bhutanese entrepreneurs face in the global market. By using secondary data involving the information pertaining to economic environment of Bhutan, the study reveals that Bhutanese entrepreneurs encounter significant obstacles to going global, such as limited access to finance, a shortage of skilled workers, and complex regulatory environments. However, there are opportunities in government policies that promote entrepreneurship and regional trade agreements. The study concludes with policy recommendations to better integrate Bhutanese entrepreneurial ventures into the global market, focusing on regulatory reforms, improved access to finance, and capacity-building initiatives.
Keywords: 330; Entrepreneurship; International business; Bhutan; Challenges; Opportunities